Effect of artificial shading on performance and reproductive parameters of semi-confined young Brangus bulls - Chiquitelli Neto, Marcos; Titto, Cristiane Gonçalves; Titto, Evaldo Antonio Lencioni; Costa e Silva, Eliane Vianna da; Puoli Filho, José Nicolau Prospero; Leme, Thays Mayra da Cunha; Henrique, Fábio Luís; Pereira, Alfredo Manuel Fraco (Brazilian Journal of Veterinary Research and Animal Science, 2015)
Thirty Brangus bulls were used in a 90-d study to assess the effect of artificial shading on the performance and reproductive characteristics of semi-confined cattle. Animals were kept in four one-ha paddocks in two groups of eight for shade treatment (5 m2/animal of 80% solar block shade cloth) and two groups of seven animals in no-shade treatment. Each treatment had two homogeneous groups, each divided into heavy-bulls (351-450 kg) and light-bulls (300-350 kg). Time spent under shade, time standing, average daily gain, testicular development and sperm quality were investigated. Animals spent 24% of the daylight under the shade and no-shaded bulls spent more time standing (P < 0.05). No difference was found in average daily gain (P > 0.05) and testicular development between shaded and no-shaded animals. However, scrotal perimeter was higher for shaded light animals compared to no-shaded light bulls (P < 0.10). Sperm motility increase during the experimental period for shaded animals (P < 0.05) and sperm abnormalities were higher for the shaded ones (P < 0.05). Although the results did not indicate pronounced benefits on cattle performance, this resource was an important alternative because it appears to provide an improvement in some reproductive parameters and ensure a better thermal comfort to the animals.